Sphingosine 1–phosphate signaling induces SNAI2 expression to promote cell invasion in breast cancer cells. Issue 6 (7th March 2019) - Wang, Wei; Hind, Tatsuma; Lam, Brenda Wan Shing; Herr, Deron R.
ABSTRACT: Epithelial‐mesenchymal transition (EMT) is a critical process implicated in the initial stage of cancer metastasis, which is the major cause of tumor recurrence and mortality. Although key transcription factors that regulate EMT, such as snail family transcriptional repressor 2 (SNAI2), are well characterized, the upstream signaling pathways controlling these transcriptional mediators are largely unknown, which limits therapeutic strategies. Sphingosine 1–phosphate (S1P) is a bioactive lipid mediator, generated by sphingosine kinases (SPHK1 and SPHK2), that mainly exerts its effects by binding to the following 5 GPCRs: S1P1 to S1P5 . S1P signaling has been reported to regulate different aspects of cancer progression including cell proliferation, apoptosis, and migration; nevertheless, its role in cancer metastasis, specifically via EMT, is not established. Here we show that SPHK1 expression correlates significantly with EMT score in breast cancer cell lines, and with SNAI2 in patient‐derived breast tumors. Cell‐based assays demonstrate that S1P can rapidly up‐regulate the expression of SNAI2 in breast cancer cells via the activation of cognate receptors S1P2 and S1P3 . Knockdown studies suggest that S1P2 and S1P3 mediate this effect by activating myocardin‐related transcription factor A (MRTF‐A) and yes‐associated protein (YAP), respectively. Michigan Cancer Foundation 7 cells stably overexpressing S1P2 or S1P3 exhibit a more invasive phenotype, when compared to control cells. Taken together, our findings suggest that S1P produced by SPHK1 induces SNAI2 expression via S1P2 ‐YAP and S1P3 ‐MRTF‐A pathways, leading to enhanced cell invasion. Cumulatively, this study reveals a novel mechanism by which S1P activates parallel pathways that regulate the expression of SNAI2, a master regulator of EMT, and provides new insights into druggable therapeutic targets that may limit cancer metastasis. Wang, W., Hind, T., Lam, B. W. S., Herr, D. R. Sphingosine 1–phosphate signaling induces SNAI2 expression to promote cell invasion in breast cancer cells. FASEB J. 33, 7180–7191 (2019). www.fasebj.org